Implementation of PAI Textbook Development Based on Religious Moderation for Students at SMKN 10 Bandung - Irfan Ahmad Zain; Ahmad Subarna; Hilman Muhammad Rofiq (al-Afkar, Journal For Islamic Studies, 2024)
Character building in students is part of the main task of the vision of national education. In the process of character building, an educator is important to instill the values of understanding religious moderation in order to foster an attitude of tolerance and a spirit of unity in everyday life. The purpose of this study was to determine the development of religious moderation-based PAI textbooks implemented in SMKN 10 Bandung students. This research uses a qualitative method with a descriptive approach by conducting observations, interviews and document studies. The results showed that students have a better understanding of religious moderation, tolerant and inclusive attitudes, and positive character based on the principles of Tawasuth, Tawazun, I'tidal, Tasamuh, Musawah, and Shura.